2008
DOI: 10.1111/j.1740-8261.2008.00368.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic Evaluation of the Omasum in Cows and Buffaloes

Abstract: The study was conducted to establish the ultrasonographic features of the healthy and impacted omasum in cows and buffaloes. Scanning was done using a 3.5 MHz microconvex transducer. In healthy buffaloes, the omasum could be scanned at the eighth to ninth intercostal space as a round or oval structure having thick echogenic wall with echogenic leaves. Gradual slow movements of omasal leaves could also be seen in real-time B-mode. The omasum appeared to be very clear, large, and close to the transducer at the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 10 publications
3
7
4
Order By: Relevance
“…At the level of seventh intercostal space from the left and right, spleen and omasum could be seen respectively in relation to reticulum. This result is in agreement with previous studies in cows and buffalo Mohindroo et al 2008).…”
Section: Discussionsupporting
confidence: 94%
“…At the level of seventh intercostal space from the left and right, spleen and omasum could be seen respectively in relation to reticulum. This result is in agreement with previous studies in cows and buffalo Mohindroo et al 2008).…”
Section: Discussionsupporting
confidence: 94%
“…The layering of the wall of the omasum as seen in the organ bath study was similar to previously reported findings [6], however, these details were observed in organ bath in only 2 healthy cows. Ultrasound waves are attenuated while traversing the thoracic wall and omasal contents, which likely resulted in the poor detail of the omasal wall and underlying structures in live animals, compared with the acoustic enhancement of details by water in the organ bath.…”
Section: Discussionsupporting
confidence: 91%
“…Exploratory laparotomy can be used to confirm a diagnosis of omasal impaction, however its invasiveness may not be suitable in already compromised patients. Ultrasonography has been proposed as a noninvasive and helpful method for subjective assessment of the normal and impacted omasum in cows and buffaloes [6, 7]. The purpose of the present study was to describe observations based on ultrasonographic examination of the omasum in an organ bath and in healthy Indian Jersey/Red Sindhi crossbred cows and to compare these results with the ultrasonographic findings in cows having omasal impaction.…”
Section: Introductionmentioning
confidence: 98%
“…Active omasal motility was not recorded in healthy cows [7] but was evident in three cows with reticulo-omasal stenosis [8]. In healthy buffalos, in which active omasal motility was distinct, the omasum appeared large and close to the abdominal wall at the start of a contraction, and then retracted from the abdominal wall and became progressively smaller [15], analogous to observations of the present study. This indicates that the contractions were in a mediolateral direction.…”
Section: Discussionsupporting
confidence: 78%
“…The omasal laminae were not seen in any of the goats. In contrast, the omasal laminae could be clearly visualised in the ovoid to spherical omasum of the buffalo [15], and in cows, the omasal laminae were sometimes seen as short echogenic cone-shaped structures protruding from the mucosal surface [7]. The laminae would probably be seen in goats with liquid omasal contents because in cattle with abomasal reflux [7], the laminae appear as fine echogenic lines running parallel to each other.…”
Section: Discussionmentioning
confidence: 99%